2012
DOI: 10.1155/2012/923925
|View full text |Cite
|
Sign up to set email alerts
|

Tai-Chi for Residential Patients with Schizophrenia on Movement Coordination, Negative Symptoms, and Functioning: A Pilot Randomized Controlled Trial

Abstract: Objective. Patients with schizophrenia residing at institutions often suffer from negative symptoms, motor, and functional impairments more severe than their noninstitutionalized counterparts. Tai-chi emphasizes body relaxation, alertness, and movement coordination with benefits to balance, focus, and stress relief. This pilot study explored the efficacy of Tai-chi on movement coordination, negative symptoms, and functioning disabilities towards schizophrenia. Methods. A randomized waitlist control design was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Six publications (Ikai et al, 2013;Scheewe et al, 2013, Manjunath et al, 2013Varambally et al, 2012;Ho et al, 2012) were considered to be of strong/good quality on both scales. Two studies (Oertel-Knöchel et al, 2014;Takahashi et al, 2012) were considered to be of weak/fair quality.…”
Section: Methodological Qualitymentioning
confidence: 99%
See 3 more Smart Citations
“…Six publications (Ikai et al, 2013;Scheewe et al, 2013, Manjunath et al, 2013Varambally et al, 2012;Ho et al, 2012) were considered to be of strong/good quality on both scales. Two studies (Oertel-Knöchel et al, 2014;Takahashi et al, 2012) were considered to be of weak/fair quality.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…Most of the included studies diagnosed schizophrenia according to the DSM criteria apart from two studies which used the ICD-10 classification criteria (Ikai et al, 2013;Heggelund et al, 2012). Three studies included both inpatients and outpatients Ho et al, 2012;Heggelund et al, 2012), two studies relied solely on outpatients (Ikai et al, 2013;Varambally et al, 2012), four studies included only inpatients (Manjunath et al, 2013;Georgiev et al, 2012;Oertel-Knöchel et al, 2014;Visceglia and Lewis, 2011), and four studies did not specify the setting (Scheewe et al, , 2012Battaglia et al, 2013;Takahashi et al, 2012). More detailed characteristics of the participants are presented in Table 1 Studies included in a meta-analysis (n=0) …”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11 Tai-chi, a well-known type of Qigong, has been criticized as being too complicated for beginners to learn and practice independently. 12 Baduanjin is another type of traditional Chinese Qigong exercise that is less physically and MING-DE CHEN, PhD YA-CHIN YEH, MS YI-JUNG TSAI, PhD YEN-CHING CHANG, PhD JUNE-WEI YU CHING-HUI HSU, MS cognitively demanding and can be learned easily and practiced without restrictions on time and space. 13,14 Previous research has demonstrated that it is feasible to offer Baduanjin as a communitybased physical exercise program for the elderly. 15 Baduanjin has also shown health benefits, such as improvements in physical fitness and quality of life, in the general population.…”
mentioning
confidence: 99%